First Field Example of Remediation of Unwanted Migration from a Natural CO2 Reservoir: The Bečej Field, Serbia. (January 2016) - Karas, D.; Demić, I.; Kultysheva, K.; Antropov, A.; Blagojević, M.; Neele, F.; Pluymaekers, M.; Orlić, B.
Abstract: The Bečej field, discovered in 1951 by the Petroleum Industry of Serbia (NIS), is one of the largest natural CO2 fields in Europe. Uncontrolled migration of CO2 out of the main reservoir, leading to subsurface seepage and surface leakage, was caused by the Bč-5 well blowout in 1968. Remediation measures were deployed in 2007 to reduce and prevent further leakage of CO2 from the Bečej natural CO2 field. To the best of our knowledge, this is the first field application of remediation measures deployed to remedy leakage from a natural CO2 reservoir – a natural analogue for an engineered geological storage site. Experiences and lessons learned from the Bečej field case are studied within the MiReCOL project (Mitigation and Remediation of CO2 Leakage). The project aims at developing a handbook of corrective measures, which can be considered in the event of significant irregularities and leakage from a CO2 storage site. We performed a comprehensive geological characterization of the Bečej field and interpreted the most recently collected monitoring data to assess the effectiveness of the remediation measures taken in 2007. A static model was constructed that comprises the main CO2 reservoir (Upper Cretaceous and Badennian) and several aquifers in the overburden (Pontian and Pliocene). Eight small hydrocarbon reservoirs are defined above the main CO2 pool at depths ranging from 450 to 900 m, suggesting that the Bečej CO2 field is a natural leaking system. The monitoring data indicate that the remediation measures were effective and have practically stopped the decline of reservoir pressure.